Alternative spatial allocation of suitable land for biofuel production in China. (November 2017) - Zhang, Jianjun; Chen, Yang; Rao, Yongheng; Fu, Meichen; Prishchepov, Alexander V.
Abstract: How to select locations for biofuel production is still a critical consideration for balance of crop and biofuel productions as well as of energy consumption and environmental conservation. Biofuels are widely produced all over the world, but this practice in China is still at the initial stage. Based on China's current stage on food security and changing biofuel demands, this paper selected agro-environmental and socio-economic factors of biofuel production, and simulated and spatially allocated areas suited for biofuel production under the two scenarios of planning-oriented scenario (PoS) and biofuel-oriented scenario (BoS) by the target year 2020. It also estimated biofuel production potentials and zones across China's provinces. The results show that land suited for biofuel production is primarily located in Northwestern, Northern, Northeastern, Central and Southwestern China, with relatively good agro-environmental conditions and medium population density, but also lower competition with crop production, aiming at facilitating governmental policy-making and multi-purpose allocation of land. Highlights: Factors are proposed for estimating land conditions for possible biofuel production. Two scenarios are setup to stimulate allocation of land suited for biofuel production. Maximum biofuel production potentials across China's provinces are estimated. Yield attainable conditions prevail the allocation decision about biofuel production.